Taxonomic review of Neorhinotora Lopes 1934 (Diptera, Heleomyzidae) - Almeida, Júlia C.; Ale-Rocha, Rosaly (Zootaxa, 2008)
Neorhinotora Lopes 1934 (Heleomyzidae, Rhinotorini) constitutes a group of rare flies distributed mainly in the Neotropical Region. The taxonomy of this genus is herein reviewed and five species are recognized: N. amapaensis Guimarães and Papavero 1966, N. aristalis (Fischer 1932), N. diversa (Giglio-Tos 1893), N. fonsecai (Lopes 1934), and N. mutica (Schiner 1868). An identification key based on morphological characters is provided for the species.